Value-Added Crackers Enriched with Red Onion Skin Anthocyanins Entrapped in Different Combinations of Wall Materials - Florina Stoica; Nina Nicoleta Condurache; Georgiana Horincar; Oana Emilia Constantin; Mihaela Turturică; Nicoleta Stănciuc; Iuliana Aprodu; Constantin Croitoru; Gabriela Râpeanu (MDPI AG, 2022)
The objective of this study was to encapsulate anthocyanins from red onion skins into different biopolymeric matrices as a way to develop powders with multifunctional activities. Two different variants of powders were obtained using a combination of gelation and freeze-drying techniques and characterized by encapsulation efficiency, antioxidant activity, phytochemical content, and color. Stability during storage and the bioavailability of anthocyanins in the in vitro simulated digestion were also examined. Powder V2, with a higher concentration of polysaccharides than V1, allowed a better encapsulation efficiency (90.53 ± 0.29%) and good stability during storage. Both variants had a high content of phytochemicals and antioxidant activity. In vitro investigations proved that an increased polysaccharides concentration offers the best protection for anthocyanins. Thus, a controlled release of the anthocyanins in the intestinal medium was achieved. The powder with the highest encapsulation efficiency was added to crackers, followed by phytochemical characterization to assess its potential added value. The addition of the micro-particles improved the functional characteristics such as antioxidant activity, showing its suitability for the development of bakery products. The attained results may bring implicit benefits to consumers, who can benefit from improved bioactive concentrations in foodstuffs, with significant health benefits.